Coastal Areas as Learning Resources to Enhance Regional Potential Understanding: A Study in Pesisir Selatan District - Muhammad Arif; Enok Maryani; Mamat Ruhimat; Dede Sugandi (Yayasan Keluarga Guru Mandiri, 2024)
The coastal zone consists of a diverse range of resources. This area's ecosystems are also quite complex and dynamic. Information about the coastal zone is necessary to provide knowledge to readers, which will be helpful for conservation efforts, sustainable planning and development, further research, and fostering coastal environmental literacy. This study aims to collect information about the resources present in the coastal zone and then integrate it into relevant learning materials such as geography. This research is a narrative review literature study. Secondary data was obtained from the Fisheries and Marine Affairs Office of West Sumatra Province, along with relevant scientific articles. Several related articles and government documents were collected, analyzed, and summarized in the body of this article. The information concerning appropriate geography learning materials was then analyzed to produce relevant content diagrams. The results of the literature review show that coastal zone resources include mangrove areas, coral reefs, seagrass beds, biodiversity, and marine tourism. Some geography learning materials for secondary school levels in Indonesia include marine and coastal materials, hydrodynamics, coastal and marine pollution, natural resources, biodiversity, ecosystems, flora and fauna, environmental and population geography, and tourism geography. The findings of this research can serve as a reference for researchers and practitioners to develop and integrate the potential of coastal areas into relevant learning.